Bagaimana Kualitas Administrasi dan Promosi Berpengaruh terhadap Kepuasaan Konsumen Pemakai Jasa Layanan Grab Online? - Mukhammad Idrus; Thamrin Tahir; Nur Arisah (Journal of Economic Education and Entrepreneurship Studies, 2021)
Technology is very familiar and continues to grow, the grab application is an application that uses technology. This study is intended to detail the impact of trust factor, managerial quality, knowledge of self-esteem and advancement on buyer's persistence factor. The information collection procedure used in this exploration is through review/concentration with a direct test information assessment strategy using the SPSS application. The population in this study were students who used translation services spread across several metropolitan areas up to 28 people. This research shows that the trust factor, administrative quality, value insight and overall progress do not have a positive effect on consumer loyalty, which means that each independent factor does not affect the level of consumer loyalty.